Topical Hesperidin Improves Epidermal Permeability Barrier Function and Epidermal Differentiation in Normal Murine Skin - Hou, Maihua (2012)
Orange peel extract appears to exhibit beneficial effects on skin whitening, inflammation, UVB protection, as well as keratinocyte proliferation. In the present study, we determine whether topical hesperidin influences epidermal permeability barrier function and its underlying mechanisms. Hairless mice were treated topically with 2% hesperidin or 70% ethanol alone twice daily for 6 days. At the end of treatment, basal barrier function as well as transepidermal water loss (TEWL) was measured 2 and 4 hours post barrier disruption. Epidermal proliferation and differentiation were evaluated by immunohistochemical staining and Western blot analysis. Additionally, lamellar body density and secretion were assessed by electron microscopy. Although there were no significant differences in basal barrier function, in comparison to control animals, topical hesperidin significantly accelerated barrier recovery at both 2 and 4 hours after acute barrier abrogation. Enhanced barrier function in hesperidin-treated skin correlated with stimulation of both epidermal proliferation and differentiation, as well as enhanced lamellar body secretion. These results indicate that topical hesperidin enhances epidermal permeability barrier homeostasis at least in part due to stimulation of epidermal proliferation, differentiation, as well as lamellar body secretion.